Gene4HL: An Integrated Genetic Database for Hearing Loss - Huang, Shasha; Zhao, Guihu; Wu, Jie; Li, Kuokuo; Wang, Qiuquan; Fu, Ying; Zhang, Honglei; Bi, Qingling; Li, Xiaohong; Wang, Weiqian; Guo, Chang; Zhang, Dejun; et al. (Frontiers in Genetics, 2021)
Hearing loss (HL) is one of the most common disabilities in the world. In industrialized countries, HL occurs in 1–2/1,000 newborns, and approximately 60% of HL is caused by genetic factors. Next generation sequencing (NGS) has been widely used to identify many candidate genes and variants in patients with HL, but the data are scattered in multitudinous studies. It is a challenge for scientists, clinicians, and biologists to easily obtain and analyze HL genes and variant data from these studies. Thus, we developed a one-stop database of HL-related genes and variants, Gene4HL (http://www.genemed.tech/gene4hl/), making it easy to catalog, search, browse and analyze the genetic data. Gene4HL integrates the detailed genetic and clinical data of 326 HL-related genes from 1,608 published studies, along with 62 popular genetic data sources to provide comprehensive knowledge of candidate genes and variants associated with HL. Additionally, Gene4HL supports the users to analyze their own genetic engineering network data, performs comprehensive annotation, and prioritizes candidate genes and variations using custom parameters. Thus, Gene4HL can help users explain the function of HL genes and the clinical significance of variants by correlating the genotypes and phenotypes in humans.